Web-Based Decision Support System For Evaluating The Performance Of Security Guards At Pt Army Using The Simple Additive Weighting (SAW) Method: - Erlin Bilfister Waruwu; Nurul Afni; Richard Parlindungan Simanjuntak (Universitas Dehasen Bengkulu, 2026)
The manual process of evaluating security guard performance presents various challenges, such as subjective assessments, inaccurate results, and a lengthy decision-making process. This study aims to design and develop a web-based decision support system using the Simple Additive Weighting (SAW) method to facilitate the evaluation of security guard performance in an objective, rapid, and measurable manner. The SAW method was chosen because it is capable of conducting evaluations based on multiple criteria through a simple, systematic, and effective weighting process. The criteria used include attendance, honesty and responsibility, cleanliness and neatness, cooperation and leadership, as well as theoretical knowledge and the application of that knowledge. The research methods employed were observation, interviews, and literature review. The results indicate that the developed system can automatically calculate scores, generate performance rankings and ratings for security guards, and provide evaluation reports that are faster, more accurate, and more transparent. This system assists management in decision-making regarding promotions, contract renewals, issuing verbal warnings, written warnings, and even termination of employment. Thus, the implementation of the web-based Simple Additive Weighting (SAW) method can enhance the effectiveness, efficiency, and objectivity of security guard performance evaluations at PT. Army.